Tourist Satisfaction and Sustainable Homestay Management: Insights from Six Rural Communities in Western Nepal (Quest Journal of Management and Social Sciences, 2025)
Purpose: Sustainable homestay tourism promotes tourist satisfaction by contributing to environmentally conscious travelers through eco-friendly practices, while also supporting local economies and culture. There is lack of research on how homestay tourism affects local livelihoods, its economic viability compared to corporate-led tourism, including potential benefits for sustainable homestay tourism.Methodology: This study utilizes the triple-bottom-line theory and integrated sustainability approaches to maximize satisfaction in homestay tourism. This study used an explanatory research design to explore the causal relationship between different variables and non-probability sampling techniques. The data collected from 267 respondents, Annapurna Rural Municipality, Kaski, was analyzed using the partial least squares structural equation modeling (PLS-SEM) version 4.0 software. Finding: The study found that tourist satisfaction in homestay tourism is influenced by leisure, financial considerations, and cultural immersion, with community involvement crucial despite challenges. This study provides valuable insights for policymakers and development partners, enabling them to understand the deriving factors of tourists' satisfaction regarding sustainable homestay tourism.Conclusion: Tourist satisfaction in homestay tourism is driven by leisure, affordability, and cultural experiences, with community involvement playing a key role. These insights help policymakers and stakeholders promote more sustainable and fulfilling homestay tourism.Keywords: Sustainable Homestay Management, Community Based Practice, Tourists’ Satisfaction, PLS-SEM 4.0, Western Nepal